Is there a role for cellular therapy in chronic lymphocytic leukemia? - Dreger, Peter (The cancer journal, 2021)
Despite multiple advances in the treatment landscape of chronic lymphocytic leukemia (CLL) during recent years, cellular therapies, such as allogeneic hematopoietic cell transplantation and chimeric antigen-engineered T cells, represent valuable therapeutic options for patients with multiply relapsed or poor-risk disease. This brief overview will summarize current results of cellular therapies in CLL including Richter transformation, suggest an indication algorithm and strategies for performing cellular therapies in these conditions, and discuss the impact of COVID-19 (coronavirus disease 2019) on allogeneic hematopoietic cell transplantation and chimeric antigen-engineered T cells in CLL.